Short-term safety results from compassionate use of risdiplam in patients with spinal muscular atrophy in Germany - Hahn, Andreas; Thiemer, René; Ludolph, Albert C.; Schwartz, Oliver; Trollmann, Regina; Weydt, Patrick; Weiler, Markus; Mellert, Kathrin Gertrud; Schwaderer, Martin Sebastian; Hagenacker, Tim (Orphanet journal of rare diseases, 2022)
The oral, selective SMN2-splicing modifier risdiplam obtained European approval in March 2021 for the treatment of patients ≥ 2 months old with a clinical diagnosis of 5q-associated spinal muscular atrophy (SMA) 1/2/3 or with 1-4 SMN2 gene copies. For the preceding 12 months, this compassionate use program (CUP) made risdiplam available to patients with SMA1/2 in Germany who could not receive any approved SMA therapy.
Gesehen am 30.11.2022